PENGARUH KAPASITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI, DAN PERAN AUDITOR INTERNAL TERHADAP KUALITAS PELAPORAN KEUANGAN PEMERINTAH DAERAH (STUDI PADA SKPK BANDA ACEH) - Zumaira, Tasya; Rahmawaty, Rahmawaty (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
This study aims to examine the effect of Human Resource Capacity, Utilization of Information Technology, and the Role of Internal Auditors on the Quality of Local Government Financial Reporting. The population used in this study were 44 Local Government Working Units (SKPK) located in Banda Aceh. Respondents in this study were employees who performed accounting or financial administration functions consisting of the Head of the Finance Subdivision, Revenue Treasurer, Expenditure Treasurer, and Staff of the Finance Section of each SKPK. The data collection method in this study used a questionnaire technique. The validity test used the Pearson Correlation test, while the reliability test used Cronbach's Alpha. The data analysis technique used is simple regression analysis with the help of the latest version of IBM SPSS software. The results of this study indicate that (1) Human Resource Capacity, Utilization of Information Technology, and the Role of Internal Auditors simultaneously affect the Quality of Local Government Financial Reporting, (2) Human Resource Capacity does not affect the Quality of Local Government Financial Reporting, (3) Utilization of Information Technology has a positive effect on the Quality of Local Government Financial Reporting, (4) the role of Internal Auditors does not affect the Quality of Local Government Financial Reporting.